2022
DOI: 10.3390/bios12060405
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Lab-On-Chip for Cancer Cell Detection through Impedance and Photoelectrochemical Response Analysis

Abstract: In this study, a biochip was fabricated using a light-absorbing layer of a silicon solar element combined with serrated, interdigitated electrodes and used to identify four different types of cancer cells: CE81T esophageal cancer, OE21 esophageal cancer, A549 lung adenocarcinoma, and TSGH-8301 bladder cancer cells. A string of pearls was formed from dielectrophoretic aggregated cancer cells because of the serrated interdigitated electrodes. Thus, cancer cells were identified in different parts, and electron–ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 88 publications
(89 reference statements)
0
15
0
Order By: Relevance
“…Impedance sensors can also identify cancer cells that are affected by drugs. A biosensor combining impedance and photoelectrochemical analysis of cancer cells was designed, as shown in Figure 1d [33], where monocrystalline silicon was used as a substrate for the biosensor. The serrated interdigitated electrodes not only can focus cells but also sense impedance signals.…”
Section: Silicon-based Impedance Biosensorsmentioning
confidence: 99%
“…Impedance sensors can also identify cancer cells that are affected by drugs. A biosensor combining impedance and photoelectrochemical analysis of cancer cells was designed, as shown in Figure 1d [33], where monocrystalline silicon was used as a substrate for the biosensor. The serrated interdigitated electrodes not only can focus cells but also sense impedance signals.…”
Section: Silicon-based Impedance Biosensorsmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) is another photoemission mechanism that can be exploited for the detection and quantification of the target analyte in LoC-based systems [ 75 , 76 , 77 ]. It is usually observed during the application of a potential (several volts) to the electrodes of an electrochemical cell that contains a solution of luminescent species (polycyclic aromatic hydrocarbons, metal complexes, Quantum Dots or Nanoparticles) in an aprotic organic solvent [ 78 ].…”
Section: Evaluation Of System Performancesmentioning
confidence: 99%
“…Barbeiro et al (2019) used NBI to study gastrointestinal endoscopy and found that NBI can be used as an important auxiliary image for WLI, which can improve the detection of gastrointestinal lesions. Apart from CAD, many biosensors have been recently researched to detect different cancer types [ 35 , 36 , 37 ]. However, most of these biosensors have a high limit of detection, thereby leading to poor sensitivity in early-stage cancer detection.…”
Section: Introductionmentioning
confidence: 99%